2007
DOI: 10.1007/s10826-007-9149-y
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Stimulant Medication and Behavioral Interventions for the Treatment of Attention Deficit Hyperactivity Disorder: A Survey of Parents’ Knowledge, Attitudes, and Experiences

Abstract: We examined parents' knowledge, attitudes, and information sources regarding Attention-Deficit/Hyperactivity Disorder (ADHD), including treatment with stimulant medication and behavioral interventions. Responses from parents with a child diagnosed with ADHD and parents without a child diagnosed with ADHD were also compared. Participants consisted of 146 parents of elementary age children from Wisconsin. The surveyed parents were aware of issues surrounding ADHD and the use of stimulant medication, but there we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…As hypothesized, we found that past experience with ADHD treatment increased parental medication willingness, consistent with previous studies (Stroh et al, 2008). However, against our expectation, adolescents’ previous ADHD treatment experience was not associated with notable differences in treatment willingness for any treatment modality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As hypothesized, we found that past experience with ADHD treatment increased parental medication willingness, consistent with previous studies (Stroh et al, 2008). However, against our expectation, adolescents’ previous ADHD treatment experience was not associated with notable differences in treatment willingness for any treatment modality.…”
Section: Discussionsupporting
confidence: 92%
“…Studies of parent ADHD treatment acceptability have consistently found higher ratings for behavioral than for medication interventions (Johnston et al, 2008; Krain et al, 2005). Parents of children with ADHD rate medication treatments as more effective than parents without personal experiences (Gage & Wilson, 2000; Stroh et al, 2008). According to Gage (2000), parents raising a child with ADHD were more likely to support a multimodal approach to treatment than parents without the personal experience.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to identify children with ADHD and implement special educational approaches to help them overcome any academic and psychological difficulties. As a result of their daily contact with children, teachers and other school personnel are in a central position to suggest further assessment for children of potential ADHD (Sax & Kautz, 2003;Snider, Busch, & Arrowood, 2003;Stroh, Frankenberger, Cornell-Swanson, Wood, & Pahl, 2008). Therefore, it is important that working teachers are adequately prepared to meet the needs of students with ADHD in their classrooms and contribute to the treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…That is, some studies report that parents of children with ADHD provide positive evaluations of medication treatment (e.g., dosReis et al, 2003; Gage & Wilson, 2000), whereas other studies report that medication is not well accepted (Pescosolido, Perry, Martin, McLeod, & Jensen, 2007). Likewise, most studies report that parents rate behavioral treatments as acceptable (e.g., Johnston et al, 2008), but not all studies are consistent (Pemberton & Borrego, 2007; Stroh, Frankenberger, Cornell-Swanson, Wood, & Pahl, 2008). Our study suggests that these discrepancies may reflect heterogeneity among the parents in that, across parents, different attributes seem to be important in driving treatment decisions.…”
Section: Discussionmentioning
confidence: 99%